(untitled) (Costos y Gestión, 2020)
Global trends such as the sustainability of organizational practices, adherence to international standards and waste reduction are perceived in the demands of society through legislative pressure and the demand for information transparency on responsible actions with the environment and in accordance with interests of your interest groups. Aware of the importance of reducing the impact of activities on the environment and competing in a globalized environment that requires sustainability protocols, our country’s organizations have begun to inventory greenhouse gases by quantifying the emission sources for development of the life cycle of goods together with the natural and energy resources used for it. The purpose of our work is to determine the environmental effects of the adoption of the distance modality in the degree courses of an Argentine public management university in order to verify the reduction that is made on the emission of greenhouse gases -GHG - and the decrease in transportation costs corresponding to students. The results show a significant saving in the indirect effects of GHG, such as student mobility and transportation costs, while for direct effects, savings are concentrated in the reduction of energy consumption of luminaires and computer equipment.